Group Cohesiveness, and Its role in Increase Collective Efficacy and Work Achievement - Endang - Sulistiyani; Sri Eka Sadriatwati; Sri Marhaeni Salsiyah; Erika - Devi; Umar - Farouk (Admisi dan Bisnis, 2022)
The purpose of this study is to analyze several antecedent variables that affect the performance of the work group in star hotels in Central Java. The sample of this research is the functional team from each work division consisting of managers as group leaders, supervisors and functional staff as group members. Methods of data collection by distributing questionnaires, interviews, observation and literature study. Data were analyzed using Structural Equation Modeling techniques. Based on statistical results, the six hypotheses that have been proposed show a significant positive effect on all relationships between variables and the two hypotheses have no effect. The indirect effect of the independent variable on group achievement produces one strategy, which is to link group cohesiveness to group achievement through Valuntary adhocratic capability. The dominant influence between variables is shown from the relationship between group cohesiveness and group achievement.